(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Rapid expansion of the export has added stimulus to the growth of local demand which led to the establishment of a number of large manufacturing industries. Grouping of provinces is needed to see which provinces have the biggest and smallest contribution in Indonesia’s export activities. A province with a small contribution can pay more attention to capacity, facilities and port access and attract domestic and foreign investors to invest in the province. Then export activities can be evenly distributed in every province in Indonesia. Therefore, the authors grouped the provinces in Indonesia using the Hierarchical Cluster Analysis method. The sample in this study is data on the value of Indonesian exports according to the loading port in the province of origin of goods (million US ), the loading port in other provinces (million US ), domestic investment (million US ), and foreign investment (million US ) in January - March 2020. The results of this study are obtained 5 clustering results with the number of members in cluster 1 as many as 29 provinces, namely provinces. In cluster 2 there were 2 provinces. In the third cluster there were 1 province. In cluster 4 there were 1 province. Whereas in cluster 5 there were 1 province.